'Let us conquer space': Visual thinking as nation building in the early United States. (July 2022) - Schulten, Susan
Abstract: The visualization of spatial knowledge is so common today that we rarely give it a second thought. But it depends upon the fairly recent recognition that maps are not just representations of the landscape, but also tools of analysis. By the end of the eighteenth century, Americans and Europeans began to use maps and other graphic tools to harvest data about the natural world. In the United States, this experimentation was prompted by political independence and the attendant need to govern the population, master the natural environment, facilitate white settler expansion, and establish agricultural self-sufficiency. To navigate this volatility, individuals began to experiment with visual and spatial representation from 1790 to the 1810s, and when considered together their efforts suggest a new era of visual thinking.